Perancangan Sistem Enterprise Resource Planning Modul Sales Pada Distributor Beras Ud Manis - Dana Marsetiya Utama; Ferry Yulianto (Department Industrial Engineering, University of Muhammadiyah Malang, 2014)
UD Manis is a rice distributor in Lamongan. The problem faced by UD Manis is having no information system for notifying stock in warehouse and customer order although company has used MS Access database. Company requires information system for notifying stock and integrating across department. There are 3 major steps in module sales in Enterprise Resource Planning (ERP) which are data collection, process planning and testing, & evaluation. The result of ERP system design particularly for module sales by using software package “Adempiere” has process sequence as sales order, shipment, invoice, and payment. Testing result of ERP system design using Adempiere shows that warehouse and sales department could check actual stock in warehouse more agile and accurate.